Early Post-Operative Endoscopy Is Associated with Lower Surgical Recurrence of Crohn’s Disease: A Retrospective Study of Three Successive Cohorts - Caroline Amicone; Carla Coimbra Marques; Catherine Reenaers; Catherine Van Kemseke; Laurence Seidel; Edouard Louis (Gastroenterology Research and Practice)
Background. The severity of endoscopic recurrence during the first year after intestinal resection for Crohn’s disease is predictive of clinical recurrence. The aim of our study was to assess the impact of the implementation of an ileocolonoscopy during the first year after surgery on surgical recurrence. Methods. All patients who underwent a first intestinal resection for Crohn’s disease between 1992 and 2018 at the University Hospital of Liège were retrospectively included. The time to surgical recurrence was compared in three successive groups of patients operated on in the period 1992–2001 (group A), 2002–2011 (group B), and 2012–2020 (group C) using the Kaplan–Meier method and the Log-Rank test. To identify independent prognostic factors, a multivariate analysis was used via the Cox model. Results. 223 patients (group A = 69, group B = 94, group C = 60) were included. Probabilities of surgical recurrence were significantly lower in group C (2.2% and 4.7% at 3 and 5 years, respectively) compared with group B (4.2% and 7.6% at 3 and 5 years, respectively) and with group A (9% and 18.2% at 3 and 5 years, respectively) (p=0.0089). Ileocolonoscopy during the year after surgery was associated with a significantly reduced surgical recurrence rate in univariate and multivariate analysis (HR = 0.31, p=0.0049). Conclusion. The implementation of an early ileocolonoscopy after surgery for Crohn’s disease since early 2000 has been associated with a reduced surgical recurrence over the last 30 years.